2001
DOI: 10.1016/s1074-5521(01)00016-3
|View full text |Cite
|
Sign up to set email alerts
|

Potent estrogen agonists based on carborane as a hydrophobic skeletal structure

Abstract: Further development of the potent carborane-containing estrogenic agonists described here, having a new skeletal structure and unique characteristics, should yield novel therapeutic agents, especially selective estrogen receptor modulators. Furthermore, the suitability of the spherical carborane cage for binding to the cavity of the estrogen receptor-alpha ligand-binding domain should provide a basis for a similar approach to developing novel ligands for other steroid receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(115 citation statements)
references
References 34 publications
2
113
0
Order By: Relevance
“…[3][4][5] We have reported applications of carboranes in medicinal drug design as a hydrophobic component of biologically active molecules, 6) targeting nuclear receptors, such as estrogen receptor (ER), 7,8) androgen receptor (AR), 9,10) retinoic acid receptor (RAR) 11,12) and retinoid X receptor (RXR).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] We have reported applications of carboranes in medicinal drug design as a hydrophobic component of biologically active molecules, 6) targeting nuclear receptors, such as estrogen receptor (ER), 7,8) androgen receptor (AR), 9,10) retinoic acid receptor (RAR) 11,12) and retinoid X receptor (RXR).…”
Section: Notesmentioning
confidence: 99%
“…1,2) Biomedical applications of the carboranes, e.g., in boron neutron capture therapy (BNCT), are of great interest. [3][4][5] We have reported applications of carboranes in medicinal drug design as a hydrophobic component of biologically active molecules, 6) targeting nuclear receptors, such as estrogen receptor (ER), 7,8) androgen receptor (AR), 9,10) retinoic acid receptor (RAR) 11,12) and retinoid X receptor (RXR). 13) It was suggested that the carborane cage works as a hydrophobic group for binding to the hydrophobic cavity of the ligand-binding domain (LBD) on the nuclear receptors, and that hydrophobic van der Waals contacts along the spherical carborane cage produce a stronger interaction than that in the case of the native ligand.…”
mentioning
confidence: 99%
“…It was reported that the C-and D-rings of E2 play an important role in stabilizing the ligand-receptor complex by the hydrophobic interactions. 22,23) In the case of NPs 6-8, the dimethyl or ethyl branch on the γ-or δ-carbon might play a role in the hydrophobic C and/ or D ring of E2.…”
Section: Relationship Between Estrogenic Activity and Structure Of Nomentioning
confidence: 99%
“…Indeed, carborane-containing ligands exhibited the enhanced binding affinities to a number of receptors/enzymes proteins (e.g., estrogen receptor, androgen receptor, HIV protease) compared to non-carborane ligands. [5][6][7][8][9][10][11] Despite the utilization of closo-carboranes as hydrophobic scaffolds in drug design and as boron-delivery moieties for BNCT has expanded, in silico molecular modeling of carborane-containing molecules with macromolecules including docking studies, scoring functions and virtual screening have been rarely reported.…”
Section: 4mentioning
confidence: 99%